Spatial Analysis of Vegetation Index in Ambon City Center Area, Indonesia using Sentinel-2 Satellite Imagery in Google Earth Engine - Rifai , Ahmat; Halim; Rakuasa, Heinrich; Tade , Ferdi; Purnama , Aventus; Jufriansah , Adi; Khusnani , Azmi (Frontiers in Sustainable Science and Technology, 2025)
This study analyzed the impact of urbanization on vegetation cover in Ambon City using Google Earth Engine (GEE) technology and the NDVI index. The methods used include Sentinel-2 image data processing and field validation at 40 sample points conducted in Google Earth Engine. The analysis revealed that the Non-vegetation area has a percentage area of 29.25%, Sparse vegetation area of 19.89%, Medium Vegetation area of 21.80% and Dense Vegetation area of 29.06% of the total area of Ambon City center. The results of this study emphasize the urgent need for conservation policies and utilization of monitoring technology in the planning of sustainable green open space in Ambon City Center.